Optimization of pediatric chest radiographic images using optical densities ratio - Souza, Rafael T. F.; Pina, Diana R.; Duarte, Sérgio B.; Miranda, José R. A. (Revista Brasileira de Física Médica, 2015)
The aim of this study is the optimization of radiographic images for the pediatric patients in the age range between 0 and 1 years old, through Optical Density Ratio (ODR), considering that pediatric patients are overexposed to radiation in the repeated attempts to obtain radiographic images considered of good quality. The optimization of radiographic techniques was carried out with the RAP-PEPP (Realistic Analytical Phantom coupled to homogeneous Phantom Equivalent to Pediatric Patient) phantom in two incubators and one cradle. The data show that the clinical routine radiographic techniques generate low-quality images at up to 18.8% when evaluated by the ODRs, and increases in doses up to 60% when compared to the optimized techniques doses.